Annual Management Education Convention 2016 on Transforming India into a Knowledge Society:The Role of Management Education - Mohanty, Subhransu Sekhar (SFIMAR Research Review, 2015)
The essential ingredients of a Knowledge Society are: Innovation, Knowledge Development, Knowledge Management, its Delivery and Applications for the benefit of all, while keeping in mind universality, liberty and equality. In this respect, management Education can certainly play a vital role in the transformation of India into a Knowledge Society by providing a life-skill approach to leadership, critical thinking, innovation, and ability to collaborate, negotiate and network. Management Education is all about leading from the front, to build a cohesive workforce that is future-ready and can navigate well through cultural diversity, customer demands and disruptive technologies, societal and environmental challenges, beyond national boundaries, in a globalized era. The concept of a management educator has shifted to that of ‘guide on the side’ rather than ‘sage on the stage’. The concept of Student Success and applied skills should be viewed as a lifelong endeavour. Given the velocity and type of data flows and the rise of Internet of Things (IOT) and Information and Communication Technology (ICT), students need to be trained to take real-time or near real-time decisions, both short-term and long-term. Management education can bring together intellectual capital and potential employers to identify future trends and required skills sets for developing students into leaders, who in turn, can put enduring opportunity within the reach of people. Investment in the Management Education Sector, as well as attracting, developing and retaining talent is vital for knowledge development and reaping its economic and social benefits.